2010
DOI: 10.5194/nhess-10-1021-2010
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami hazard assessment in the Ionian Sea due to potential tsunamogenic sources – results from numerical simulations

Abstract: Abstract. In spite of the fact that the great majority of seismic tsunami is generated in ocean domains, smaller basins like the Ionian Sea sometimes experience this phenomenon. In this investigation, we study the tsunami hazard associated with the Ionian Sea fault system.A scenario-based method is used to provide an estimation of the tsunami hazard in this region for the first time. Realistic faulting parameters related to four probable seismic sources, with tsunami potential, are used to model expected cosei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…In the last decade, several studies have been made in western Greece in order to reconstruct the Holocene coastal and environmental changes (Kontopoulos and Avramidis, ; Kraft et al ., ; Poulos et al ., ; Kelletat, ; Cundy et al ., ; Vött, ; Avramidis et al ., ; Scheffers et al ., ; Vött et al ., ; Avramidis and Kontopoulos, ; Kontopoulos and Koutsios, ). Coastal and lagoon sedimentation in western Greece has regularly been influenced by Holocene tsunami inundations (Kontopoulos and Avramidis, ; Scheffers et al ., ; Vött et al ., ), while a resent tsunami hazard assessment for the Ionian Sea has been proposed by Tselentis et al ., ().…”
Section: Geological and Tectonic Settingmentioning
confidence: 99%
“…In the last decade, several studies have been made in western Greece in order to reconstruct the Holocene coastal and environmental changes (Kontopoulos and Avramidis, ; Kraft et al ., ; Poulos et al ., ; Kelletat, ; Cundy et al ., ; Vött, ; Avramidis et al ., ; Scheffers et al ., ; Vött et al ., ; Avramidis and Kontopoulos, ; Kontopoulos and Koutsios, ). Coastal and lagoon sedimentation in western Greece has regularly been influenced by Holocene tsunami inundations (Kontopoulos and Avramidis, ; Scheffers et al ., ; Vött et al ., ), while a resent tsunami hazard assessment for the Ionian Sea has been proposed by Tselentis et al ., ().…”
Section: Geological and Tectonic Settingmentioning
confidence: 99%
“…Minimum wave heights calculated for boulder dislocation at the study sites, correspond to results reported from south‐eastern Sicily (Scicchitano et al ., ; Barbano et al ., ) and from southern Apulia (Mastronuzzi et al ., ). Numerical simulations of tsunami wave propagation in the Gulf of Kyparissia, underline the possibility of tsunami wave heights high enough to initiate boulder movement (Tselentis et al ., ; Röbke et al ., ).…”
Section: Discussionmentioning
confidence: 96%
“…Besides tsunamis caused by local offshore faults or submarine slides, potential impact of teletsunamis have to be considered for the western Peloponnese, such as the AD 365 event triggered by an earthquake that took place offshore western Crete (Papadopoulos et al, 2014a). Moreover, the coastline of the Gulf of Kyparissia is directly exposed to the Hellenic Trench which is located only 70 to 80 km offshore (Papanikolaou et al, 2007), and to the Filiatra and Zakynthos faults (Tselentis et al, 2010). Moreover, due to its position southward of the protecting Ionian Islands, the gulf is open towards the central Ionian Sea.…”
Section: Introductionmentioning
confidence: 99%